Prefrontal cortex activation during neuropsychological tasks might predict response to pharmacotherapy in patients with obsessive–compulsive disorder - Takeda T (Dove Medical Press, 2017)
Tomoya Takeda,1 Satsuki Sumitani,2 Sayo Hamatani,1 Yosuke Yokose,3 Megumi Shikata,4 Tetsuro Ohmori5 1Department of Psychiatry, Tokushima University Hospital, 2Department of Support for Students with Special Needs, Institute of Biomedical Sciences, Tokushima University Graduate School, 3Taoka Higashi Hospital, Tokushima, 4Department of Psychiatry, Ibogawa Hospital, Tatsuno, 5Department of Psychiatry, Institute of Biomedical Sciences, Tokushima University Graduate School, Tokushima, Japan Objective: We investigated oxyhemoglobin change in the prefrontal cortex (PFC) of patients with obsessive–compulsive disorder (OCD) who showed different responses to pharmacotherapy during neuropsychological tasks with near-infrared spectroscopy. Subjects and methods: A total of 42 patients with OCD (mean age: 35.6±9.6 years, 14 men, 28 women) and healthy control subjects (mean age: 35.4±9.7 years, 13 men, 29 women) were selected. Patients with OCD were divided into three groups (responders to selective serotonin-reuptake inhibitors (SSRIs), responders to SSRIs with antipsychotics, and nonresponders to SSRIs and SSRIs with antipsychotics) based on pharmacological response. We investigated oxyhemoglobin change in the PFC of subjects during Stroop tasks and a verbal fluency test with near-infrared spectroscopy. Results: Responders to SSRIs showed smaller activation compared to control subjects during the Stroop incongruent task and verbal fluency test, but not during the Stroop congruent task. In contrast, responders to SSRIs with antipsychotics showed smaller activation compared to control subjects during all three tasks. Conclusion: Our results suggest that activation of the PFC during Stroop tasks might predict responses to pharmacotherapy of patients with OCD. Keywords: obsessive–compulsive disorder, pharmacotherapy, near-infrared spectroscopy, Stroop task, verbal fluency test